Molecular cytogenetic delineation of deletions and translocations involving chromosome band 7q22 in myeloid leukemias - Döhner, Konstanze; Fröhling, Stefan; Scherer, Stephen W.; McAllister Brown, Jill; Scholl, Claudia; Stilgenbauer, Stephan; Tsui, Lap-Chee; Lichter, Peter; Döhner, Hartmut (Blood, 1997)
Loss of chromosome 7 (−7) or deletion of its long arm (7q−) are recurring chromosome abnormalities in myeloid disorders, especially in therapy-related myelodysplastic syndrome (t-MDS) and acute myeloid leukemia (t-AML). The association of −7/7q− with myeloid leukemia suggests that these regions contain a novel tumor suppressor gene(s) whose loss of function contributes to leukemic transformation or tumor progression. Based on chromosome banding analysis, two critical regions have been identified: one in band 7q22 and a second in bands 7q32-q35. We analyzed bone marrow and blood samples from 21 patients with myeloid leukemia (chronic myeloid leukemia, n = 2; de novo MDS, n = 4; de novo AML, n = 13; t-AML, n = 2) that on chromosome banding analysis exhibited deletions (n = 19) or reciprocal translocations (n = 2) of band 7q22 using fluorescence in situ hybridization. As probes, we used Alu-polymerase chain reaction products from 22 yeast artificial chromosome (YAC) clones that span chromosome bands 7q21.1-q32, including representative clones from a panel of YACs recognizing a contiguous genomic DNA fragment of 5 to 6 Mb in band 7q22. In the 19 cases with deletions, we identified two distinct commonly deleted regions: one region within band 7q22 was defined by the two CML cases; the second region encompassed a distal part of band 7q22 and the entire band 7q31 and was defined by the MDS/AML cases. The breakpoint of one of the reciprocal translocations was mapped to 7q21.3, which is centromeric to both of the commonly deleted regions. The breakpoint of the second translocation, which was present in unstimulated bone marrow and phytohemagglutinin-stimulated blood of an MDS patient, was localized to a 400-kb genomic segment in 7q22 within the deletion cluster of the MDS/AML cases. In conclusion, our data show marked heterogeneity of 7q22 deletion and translocation breakpoints in myeloid leukemias, suggesting the existence of more than one pathogenetically relevant gene.
Elektronische Reproduktion der Druck-Ausgabe 14. Dezember 2020
Gesehen am 30.10.2024